Preparation and characterization of polyaniline graphene nanoplatelets conductive nanocomposite for wearable textile antenna - Khalid, Nor Aisah (2024)
Wearable textiles for antennas have growth significantly due to their widespread utilization in comprehensive monitoring, communication and storage systems. Traditional antennas are often bulky and susceptible to corrosion, but the integrating antenna into textiles offers a promising solution for wearable applications. This study explores the use of polyaniline (PANI) combined with graphene nanoplatelets (GNPs) at various loading (0.25 wt%, 0.50 wt%, 0.75 wt% and 1.00 wt%) to create a conductive polymer via oxidative polymerization, aimed at enhancing wireless communication function in electronics devices. Ammonium persulfate (APS) was used as an oxidizing agent in hydrochloric acid (HCl) and aniline monomers were polymerized into elongated PANI chains. Non covalent surface modification technique including π-π stacking, van der Waals forces and electrostatic interactions preserved the GNPs lattice and enhanced the electrical conductivity by charge carrier mobility, resulting in superior antenna characteristics. Screen printing techniques were employed to integrate these materials into wearable structures without compromising antenna performance. A rectangular microstrip patch antenna design, simulated with CST Microwave Studio was printed using a PANI/GNPs mixture mixed with ethylene glycol (EG) and polyvinyl pyrrolidones (PVP) for optimal ink adhesion. Morphological analysis (SEM, FESEM and TEM) showed well-distributed and connected nanoparticles facilitating continuous electron pathways. FTIR, RAMAN and XRD characterizations confirmed the presence of carboxylic acid (COOH) and amine (NH2) groups, improved structural order and decreased crystallite size indicating enhanced charge carrier connectivity. The 0.75 wt% PANI/GNPs (treated)-DBSA sample exhibited the highest conductivity value at 22.34 S/cm. Simulation and experimental results demonstrated return loss (S11) values of -23.38 dB and -20.78 dB respectively with antenna gain of 2.86 dB at 2.45 GHz and 7.01 at 2.60 GHz. The radiation pattern illustrated a dipole shape for both the E- field and H-field. The successful synthesis of PANI/GNPs with DBSA significantly enhanced electrical conductivity, leading to an optimal conductive ink formulation for microstrip patch antenna fabrication. Experimental validation confirmed improved antenna performance, which is particularly promising for flexible and lightweight WBAN application. In conclusion, PANI/GNPs-DBSA nanocomposites offer a compelling alternative to rigid, expensive materials like copper or FR4 in antenna-based telecommunication applications, paving the way for advanced wearable technology.